Postculture - an area of pegogical activities and research. Outline of the issues - Józef Górniewicz (Studia z Teorii Wychowania)
In the article I analyze new trends in the development of culture. They do not have their own name, hence the term postculture appears as a sign of the declining form of contemporary culture. I discuss the sources of postculture, its manifestation and consequences for man, that is, the decline of authority religions values, moral values and the deprivation of cultural roots. Modern man feeds his mind with the content of elecronic and social media.